Leiomyoma cellulare in postoperative material: clinical cases - L. Sikora-Szczęśniak, Dobrosława; Sikora, Wacław; Szczęśniak, Grzegorz (Medical Studies/Studia Medyczne, 2013)
Introduction: Leiomyoma in one of the most common benign endometrial cancers. Location of the myoma in the cervix and the area of the broad ligament of the uterus is rare. Leiomyoma cellulare (LC) occurs in about 5.0% of leiomyoma cases. Aim of the research: To determine the occurrence of LC among 294 cases of myomas as well as myomas and uterine endometriosis, found in postoperative examinations. Material and methods: Patients were qualified for the surgery based on a gynaecological examination, an ultrasonographic examination and a histological assessment of scrapings from the uterine cavity. The final diagnosis was given at the Centre of Pathomorphology of the Radom Specialist Hospital in Radom, based on a microscopic examination of postoperative material. Clinical analysis was performed in 16 cases, where LC was diagnosed during postoperative examination. Results : Among the women operated on due to myomas (n = 179; 60.9%) as well as myomas and reproductive organ endometriosis (n = 115; 39.1%), LC tissue was diagnosed during histopathological examination in 9 (5.0%) and 7 (6.1%) cases, respectively. The average age of the LC patients was 45.6, whereas in patients with myomas as well as myomas and reproductive organ endometriosis it was 49.1. The average age of LC patients was significantly lower in relation to patients operated on due to reproductive organ myomas. In 87.5% of the cases, LC was found in myomas situated in the body of the uterus; and in the remaining 12.5% (2 cases), in the cervix and the area of the parametrium. Conclusions : Leiomyoma cellulare in reproductive organs concerned mainly the body of the uterus (87.4%), and sporadically the cervix (6.3%) and the area of the broad ligament of the uterus (6.3%).